(untitled) (Dissertare, 2019)
This essay put forward three purposes related to the thought and educational action of the Indian poet Rabindranath Tagore. The first purpose was to describe the sources of his philosophy and his educational practices framed in their historical context. The second purpose dealt with establishing the bonds of his educational thinking with some of the pedagogical currents of the Western world. The third purpose revolved around the connections of his educational thinking with the contemporary paradigm of human development and the capabilities approach. The method applied in the paper was critical hermeneutics. In the essay, it is concluded that Tagore’s educational thinking is valid, has similarities with nowadays current western pedagogy and has compatibility with the capabilities approach, based on the premises of creativity, freedom of thought and transforming potential of education in the individual and collective area. Due to its universalistic spirit and its validity, Tagore’s educational thought can be adopted as a reference in the formulation of policies aimed at establishing a transforming education of social reality.